A first estimation of Tsunami Hazard of the Caribbean Coast of Costa Rica from Local and Distant Seismogenic Sources - Chacon-Barrantes, Silvia (2022)
Costa Rica has experienced 41 tsunamis since 1746, 36 of them at the Pacific coast and only 5 at the Caribbean coast. However, the oldest record belongs to the Caribbean coast, as well as the only tsunami that has caused deaths in Costa Rica: the 1991 Limón tsunami.